Glycemic Variability and Diabetic Neuropathy in Young Adults With Type 1 Diabetes - Christensen, Marie Mathilde Bjerg; Hommel, Eva Elisabeth; Jørgensen, Marit Eika; Fleischer, Jesper; Hansen, Christian Stevns (Frontiers in Endocrinology, 2020)
Background Glycemic variability (GV) may attribute to the pathogenesis of diabetic neuropathy. The aim of this cross-sectional study was to investigate the association between GV and distal symmetric polyneuropathy (DSPN) and cardiovascular autonomic neuropathy (CAN) in a Danish population of young adults with type 1 diabetes. Methods Young adults between 18-24 years with type 1 diabetes were included in this cross-sectional study. CAN was assessed by cardiovascular autonomic reflex tests (CARTs) and heart rate variability (HRV). DSPN was assessed by light pressure, pain and vibration perception, electrochemical skin conductance, sural nerve conduction velocity (SNCV) and amplitude potential (SNAP). GV were obtained by continuous glucose monitoring including coefficient of variation (CV), SD, continuous overall net glycemic action (CONGA) and mean amplitude of glucose excursions (MAGE). Results The study comprised 133 young adults (43.6% males), mean age of 22 years (SD 1.6). Unadjusted, higher CV was associated with a decreased risk of sural nerve conduction (P=0.03), abnormal SNAP (P=0.04) and incidents of definite CAN (P=0.04). Likewise, higher CONGA was associated with increasing incidents of subclinical DSPN (P=0.03), abnormal SNAP (P=0.01) and SNCV (P=0.02). However, both associations were not statistically significant in the fully adjusted model. Higher MAGE was associated with slightly increasing measures of HRV (P=0.03) but only when fully adjusted. When correcting for multiple tests significance was lost. A significant association was found between HbA1c and measures of both DSPN (P<0.02) and HRV (P<0.03) in fully adjusted models. Conclusions No significant associations between GV and diabetic neuropathy were found after adjusting for risk factors and multiple tests. This suggests that GV may not be a risk factor for diabetic neuropathy in young adults with type 1 diabetes. However, long-term effects of GV excursions may still play a role in the pathogenic mechanisms leading to neuropathy in later life.